2011
DOI: 10.1128/jvi.02689-10
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus 1 Glycoprotein B and US3 Collaborate To Inhibit CD1d Antigen Presentation and NKT Cell Function

Abstract: Herpes simplex viruses (HSVs) are prevalent human pathogens that establish latency in human neuronal cells and efficiently evade the immune system. It has been a major medical challenge to eradicate them and, despite intensive efforts, an effective vaccine is not available. We previously showed that upon infection of antigen-presenting cells, HSV type 1 (HSV-1) rapidly and efficiently downregulates the major histocompatibility complex class I-like antigen-presenting molecule, CD1d, and potently inhibits its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
89
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 76 publications
5
89
0
1
Order By: Relevance
“…We and others have shown that herpes simplex virus 1 (HSV-1), the prototype alphaherpesvirus, has evolved to downregulate CD1d expression in antigen-presenting cells and evade NKT cell function (10,13,14). Furthermore, we have demonstrated that the viral protein kinase US3 is a major viral protein that downregulates cell surface expression of CD1d by suppressing its recycling (8).…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…We and others have shown that herpes simplex virus 1 (HSV-1), the prototype alphaherpesvirus, has evolved to downregulate CD1d expression in antigen-presenting cells and evade NKT cell function (10,13,14). Furthermore, we have demonstrated that the viral protein kinase US3 is a major viral protein that downregulates cell surface expression of CD1d by suppressing its recycling (8).…”
mentioning
confidence: 90%
“…The HSV-1 KOS strain expressing green fluorescent protein (GFP)-fused VP26 protein was generously provided by Prashant Desai (Johns Hopkins University, Baltimore, MD). The HeLa.CD1d cell line has been described previously (8). A rabbit monoclonal antibody (MAb) against KIF3A and a rabbit polyclonal antibody against KIF3B were purchased from Abcam.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that HSV-1 Us3, the best-studied alphaherpesvirus Us3 homologue, blocked apoptosis (16)(17)(18)(19), promoted vesicle-mediated nucleocytoplasmic transport of nucleocapsids through nuclear membranes (20)(21)(22)(23), promoted gene expression by blocking histone deacetylation (24)(25)(26), controlled infected-cell morphology (15,18,27), modulated host immune systems (28)(29)(30)(31)(32)(33)(34)(35), stimulated mRNA translation by activating mTORC1 (36), regulated intracellular trafficking of the abundant virion component UL47 (37) and the essential envelope glycopro-tein B (gB) (38,39), and upregulated the enzymatic activity of viral dUTPase (vdUTPase) (40). These observations suggested that HSV-1 Us3 is a multifunctional protein that regulates various cellular and viral functions by phosphorylating a number of cellular and viral protein substrates.…”
mentioning
confidence: 99%
“…Estas células del sistema inmune innato reconocen moléculas lipídicas polares, propias del hospedero, denominadas CD1d, las que poseen similitudes estructurales con moléculas de histocompatibilidad de clase I (MHC-I) 111 (Figura 2, panel derecho). Recientemente se ha demostrado que VHS-1 es capaz de impedir la presentación de CD1d en la superficie de células infectadas, mediante el re-direccionamiento de estas moléculas a compartimentos intracelulares 112,113 . Con ello, el virus es capaz de evadir la presentación del ligando a células NKT evitando así la actividad citotó-xica de estas células.…”
Section: El Virus Herpes Simplex Modula La Actividad De Células Nkt Y Nkunclassified